Lamella-inspired 3D Concrete Printed Column-slab System: Balancing Act for Productivity and Sustainability - Huang, Shuyi; Anton, Ana; Dillenburger, Benjamin; Xu, Weiguo (MAJ - Malaysia Architectural Journal, 2025)
3D concrete printing (3DCP) is a promising technology for building diverse cities as it can realize customized elements with an automated construction process. However, in large-scale construction, 3DCP is still facing challenges in balancing productivity and sustainability. First, the geometries that can be printed fast demand increased concrete usage to ensure stability during the printing processes. Second, geometries with material-saving potential usually involve intricate segmentation and assembly processes to ensure printable shapes. To address such conflicts, this paper develops a novel form-finding method inspired by mushroom lamellae and then proposes a column-slab system based on this method. The lamella-inspired method aims to 3DCP the geometries in their final orientation by adding support through folds introduced in the unprintable parts. From a productivity perspective, this method folds the surface of the column-slab system according to their overhang and cantilever degrees, transforming the structure into a self-supporting geometry suitable for 3DCP. From a sustainability perspective, the lamella branching pattern aligns with material-efficient structural frameworks, eliminating the unnecessary concrete inside the system. Subsequently, a 3DCP prototype and a Fused Deposition Modeling (FDM) scaled model are presented to demonstrate the feasibility of the proposed method. In conclusion, the paper outlines a comprehensive design-to-construction workflow for a 3DCP column-slab building system suitable for denser urban areas. This method considers not only material reduction of the result but also labor savings during the handling of the printed components.